2016
DOI: 10.18805/lr.v0iof.11049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic variation, diversity, and resistance to Helicoverpa armigera in cultivated chickpea (Cicer arietinum L.) undernew agro-climatic zone

Abstract: Climate change will have different impacts on various crops around the world. Rise in temperature will offer opportunity to cultivate nutritious legume crops like chickpea in new agro-climatic zones. Therefore, this study was piloted to know the genetic variation, genetic divergence, correlations and path analysis of six important quantitative traits among 25 chickpea genotypes to ascertain their potential to grow in new agro-climatic zone of North-Western Himalayas. The chickpea genotypes exhibited sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Another study revealed from the study on 70 elite lines of desi chickpea, eleven clusters were formed [13]. Genetic divergence study in 25 genotypes of chickpea and grouped them into seven clusters using Tocher's method [14]. The clustering pattern indicated that the genetic diversity was not fully associated with geographical and genetic diversity.…”
Section: Composition Of Clustersmentioning
confidence: 99%
“…Another study revealed from the study on 70 elite lines of desi chickpea, eleven clusters were formed [13]. Genetic divergence study in 25 genotypes of chickpea and grouped them into seven clusters using Tocher's method [14]. The clustering pattern indicated that the genetic diversity was not fully associated with geographical and genetic diversity.…”
Section: Composition Of Clustersmentioning
confidence: 99%